Tuberculosis in hospital environment: clinical profile in a tertiary hospital from Ceará and level of knowledge of health personnel about control measures - doi:10.5020/18061230.2010.p260 - Roberto da Justa Pires Neto; Carolina Oliveira Costa; João Bosco Breckenfeld Bastos Filho; Juliana de Melo Matos Lins; Roney Gonçalves Fechine Feitosa; Terezinha do Menino Jesus Silva Leitão; Mônica Cardoso Façanha; Valéria Goes Ferreira Pinheiro (Universidade de Fortaleza, 2012)
(TB) and to assess the knowledge of health personnel on fundamental concepts about TB and control measures for pulmonary tuberculosis in a hospital environment. Methods: The study was conducted in a tertiary hospital in Fortaleza-CE and involved patients admitted with TB and health professionals responsible for assistance. A first phase was characterized by a retrospective study of medical records of patients admitted with suspected TB. In a second stage, a cross-sectional study with application of a structured questionnaire assessed the knowledge of health personnel on TB control measures in a hospital environment. Results: Sixty-seven patients admitted with suspected TB had their medical records assessed. Among the confirmed cases, the most frequent clinical form was pulmonary (81.3%). Out of 55 patients admitted with suspected pulmonary tuberculosis, only 29 (52.7%) were admitted in a respiratory isolation bed. Twenty-six patients with suspected pulmonary tuberculosis on admission stayed a total of 148 days out of a respiratory isolation bed (average 4.1 days / patient). The knowledge of 159 health professionals about TB was assessed. Regarding the transmission of TB, 107 (67.2%) were unaware of airborne transmission and 109 (68.5%) ignored the clinical forms that require respiratory isolation. Conclusions: Pulmonary tuberculosis is the most frequent clinical form among inpatients in a tertiary hospital in Fortaleza- CE. Considerable fraction of health personnel doesn't know key concepts related to tuberculosis and essential for the proper and safe care.